2000
DOI: 10.1148/radiographics.20.4.g00jl371127
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Tissue Harmonic Imaging with Conventional US in Abdominal Disease

Abstract: Harmonic waves are generated from nonlinear distortion of an acoustic signal as an ultrasound wave insonates tissues in the body. These beams are integer multiples of a fundamental transmitted frequency. Potential advantages of harmonic imaging include improved axial resolution due to higher frequencies and better lateral resolution due to narrower beams. Decreased noise from side lobes improves signal-to-noise ratios and reduces artifacts. Deleterious effects of the body wall are also reduced. The authors pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 7 publications
1
89
0
4
Order By: Relevance
“…Due to their high frequency, the result is a high quality image. Harmonic ultrasound technique ("coded harmonics" or "tissue harmonic imaging," THI) combined with the pulse inversion procedure ("pulse inversion harmonic imaging") allows to obtain information regardless of the depth where the region of interest lies and is available on most commercial equipment (Choudhry et al, 2000).…”
Section: Tissue Investigationmentioning
confidence: 99%
“…Due to their high frequency, the result is a high quality image. Harmonic ultrasound technique ("coded harmonics" or "tissue harmonic imaging," THI) combined with the pulse inversion procedure ("pulse inversion harmonic imaging") allows to obtain information regardless of the depth where the region of interest lies and is available on most commercial equipment (Choudhry et al, 2000).…”
Section: Tissue Investigationmentioning
confidence: 99%
“…Limitations of THS are overall coarse echotexture and decreased penetration. (6,7) Previous studies by Yucel C et al (9) Sodhi K S et al (10) Choudhry S et al (11) Kubota K et al (12) evaluated efficacy of THS as compared to CS and concluded that THS was significantly superior to conventional sonography, especially in obese patients and patients with poor acoustic window. Our study correlated with these previous studies and confirmed that tissue hormonic imaging was better than conventional sonography in assessment of focal liver lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The improved image quality of THS has led to its widespread use in evaluation of the abdomen (liver, kidney, gall bladder, bile ducts), vessels and breasts [7][8][9][17][18][19][20][21][22][23][24][25][26][27]. Limitations of THS include overall coarse echo texture and decreased penetration [17,18].…”
Section: Introductionmentioning
confidence: 99%